The use of Daphnia magna immobilization tests and soil microcosms to evaluate the toxicity of dredged sediments - Miranda, Ana F. Pereira
This paper evaluates the feasibility of using the buffering capacity of natural soil for the remediation of dredged material before being disposed in soil landfills. To achieve that, an Integrated Soil Microcosms (ISM) system was designed to produce elutriates and leachates from the sediment/soil percentage mixtures. Furthermore, to investigate the biological effects of the contaminated sediments, the toxicity behavior of leachates and elutriates was assessed and compared by performing acute (48 h) toxicity assays with the cladoceran Daphnia magna as test organism. Sediment samples contaminated with industrial residues were collected in November-December 2007 in a river area under the influence of the effluents from a chlor-alkali industry (Ebro River basin in Flix Reservoir, NE Spain). Uncontaminated natural soil was collected from a pesticide-free field. Particle size, pH, conductivity, total organic carbon, organic matter content, and soil and sediment moisture were determined. Eighty ISM were set up in the laboratory. To each ISM, 3 kg of fresh soil was added to form a 20-cm deep layer. Sediment and soil were mixed in the following proportions: 0:100, 10:90, 20:80, 35:65, and 50:50 (percent sediment/soil). Five hundred grams of the mixtures were placed at the top of each microcosm to form a 10-cm deep layer. The Integrated Soil Microcosm experiment ran for 60 days. Elutriates were obtained at days 1, 7, 14, 30, and 60 while leachates were collected at days 7, 14, and 30. At each sampling time, the toxicity of the extracted elutriate and collected leachate was evaluated by performing D. magna immobilization tests. From the results, it was apparent that the toxicity of contaminated sediments decreased with the increasing percentage of fresh soil that was added as a buffer. The results also exhibited that the obtained elutriates caused significant mortalities in D. magna at day 1 and day 7, though a slight reduction in the mortality of D. magna was observed by day 30. Conversely, a different pattern of toxicity was observed in the case of the produced leachates, where no mortality of D. magna was observed at day 7, but the toxicity increased with time resulting in some mortality of D. magna by day 30. Through the leaching process, toxic contaminants present in the soil/sediment mixtures seemed to be washed out through a 30-cm soil column leading to an increased toxicity of the leachates over time and to a decreased toxicity of the soil/sediment mixtures used to obtain the elutriates. Soil microcosms using natural soil as a buffer can be used to evaluate the toxicity of contaminated sediments and also to assess the environmental impacts on soil organisms and ground waters as a result of run-off and infiltration processes. The high mortality of D. magna exposed to elutriates observed at the beginning of the experiment (day 1) indicated the presence of hazardous toxicants in the sediments collected from the Ebro River.